Le Pilotage De La Performance Des Fournisseurs Par Les Pratiques De Gestions De Chaine Logistique (Supply Chain Management) Et L’apport De L’audit Combine «Qualité-Logistique» « Cas De Renault Tanger» - Moutaoukil, Fouad; M’barki, Mohamed Amine; Boungab, Souad (European Scientific Journal, ESJ, 2018)
Based on the current economic environment of companies, with the focus on core business and the increasing use of outsourcing, a good relationship management with suppliers is very crucial to increase the performance of the companies. Since the rate of purchases in the value added of the product keeps increasing, suppliers who are considered as partners have a significant role to play. This situation poses the problem of managing the customer-supplier relationship because a greater part of the performance depends on suppliers and the service providers. Due to these observations, there is the need for companies to secure their supply chain, especially in terms of QCD (Quality, Cost and Delay). The control of these three elements is a solid asset that is used to remain competitive and to keep their strategic stake in the logistics chain. The SCM practices related to supplier management are defined as a set of activities within an organization to ensure an effective supply chain management. This paper focuses on exploring the best practices in term of supplier management used to ensure high performance in the automotive sector in Morocco. In other words, the objective of this research is to assess the actual state and the perspectives for applying a security approach and an appraisal of the suppliers’ performance, based on management practices and a combination of quality and logistics audits. This research contributes to the study of the link between the SCM practices and the performance based on a qualitative approach applied with a business case within the automobile manufacturer Renault Tanger in Morocco.